Pengembangan Pusat Kajian Pancasila Dan Kewarganegaraan Politeknik Negeri Media Kreatif Sebagai Media Pembelajaran Online - Andrian Andrian; Andriyana Andriyana (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
Online learning (Online) during the COVID-19 pandemic has become a must for every university. This is because teaching and learning activities are not allowed to do face-to-face. For this reason, we need a learning media that can be used online so that students can easily find teaching materials provided by lecturers. Lecturers of the Politeknik Negeri Media Kreatif, especially lecturers of Pancasila and Citizenship Education Courses, wish to develop a website-based learning media. With the development of a special website for Pancasila and Citizenship Education courses, it is hoped that students who take these courses can easily access learning materials. Keyword : Pancasila, Citizenship